Genotypic diversity and genetic parameters of ’Tahiti’ acid lime using different rootstocks - Malikouski, Renan Garcia; Peixoto, Marco Antônio; Ferreira, Filipe Manoel; Morais, Andréia Lopes de; Alves, Rodrigo Silva; Zucoloto, Moises; Barbosa, Dimmy Herllen Silveira Gomes; Bhering, Leonardo Lopes (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to estimate the genetic parameters and to evaluate the genotypic diversity of 12 'Tahiti' acid lime (Citrus latifolia) genotypes grafted onto two rootstocks. The experiment was carried out from July 2017 to January 2019, in the municipality of São Mateus, in the state of Espírito Santo, Brazil. Vegetative (stem diameter, canopy projection diameter, and plant height), productive (yield and fruit number), and fruit quality (fruit diameter, soluble solids content, and juice yield) traits were determined. A mixed model was used to estimate heritability and repeatability coefficients, as well as to predict clonal values. Scion diversity was determined through the standardized mean difference of Euclidean distances, and genotypes were clustered by modified Tocher. Clustering quality and trait importance were evaluated using the principal component analysis (PCA). Genotypic variance was observed, which is indicative of the possibility of selection of superior genotypes. The Tocher method showed the presence of three clusters, which is in alignment with the PCA results. The multivariate analyses allows of the selection and the recommendation of superior 'Tahiti' acid lime genotypes.